The History of Politics in Angola: From Nationalism to the Totalitarian Single-Party System - Camba, Tomás Fernando (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
The political, economic and social instabilities of the African countries have been seen as one of the biggest challenges to be overcome in the current days. Today, the lack of economic and social freedom is the great problem that makes the weak effort of the African politicians on consolidating the political and economic systems in permanent crisis, even more vulnerable. We attempt to understand the reasons of the increasing levels of bribery of the public and private institutions besides the deficit of a political ethics and other corrosive factors of the African nations that make it a continent with a high level of vulnerability. So, we task ourselves to draft a historic line of the political thought of one of the most promising countries of the African continent: Angola. This is achieved through the use of historic sources that chain the main political events of the history of Angola that led to the independence and that succeeded. It is concluded that the state intervention based on ideas socialist / communist ideas has been, as theoretically proved by the Austrian School, harmful to the socio-economic development of the African country and it is suggested a review to such intervention to be completed in a future paper.